Routine as an Extraordinary Educational Experience in the Perspective of Pragmatism - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to analyze and decode, for the theory and practice of pragmatistic education, the thought of the renowned philosopher and educator – John Dewey, and the American sociologist – Richard Sennett. Among many important concepts and solutions that can be drawn from the legacy of both philosophers, the author distinguishes the issue of routine, understood by each of the philosophers in a different way. John Dewey claims that routine leads to the blockage of human development, whereas Richard Sennett believes that routine has an educational power. These two distinct approaches to routine may be a source of instruction and inspiration for modern pedagogy as a scientific discipline.
Keywords: routine; everyday life; uncommonness; pragmatism; pedagogy